Dynamics of Criminal Case Handling: A Case Study of Minors Carrying Sharp Weapons in North Lampung - Zulham, Muhammad; Setianegara, Ery (CV. Ulil Albab Corp, 2025)
This study examines the dynamics of handling criminal cases involving children carrying sharp weapons in North Lampung. Utilizing a qualitative approach, the research aims to explore the social and legal phenomena associated with offenses committed by minors. Through in-depth interviews with judges, heads of correctional facilities, and the children involved, as well as document analysis, the study identifies challenges in law enforcement and child protection. The findings indicate that fair and rehabilitative law enforcement is crucial to prevent recidivism and provide opportunities for rehabilitation for children. This research offers recommendations for more effective policies and legal practices in addressing cases involving minors, emphasizing a more humane and collaborative approach between law enforcement and the community.